Correction: Gerber, M.; Pillay, N. Automated Design of the Deep Neural Network Pipeline. Appl. Sci. 2022, 12, 12215 - Mia Gerber; Nelishia Pillay (Applied Sciences, 2024)
The authors would like to make the following corrections to this published paper [...]